Late results of Hirschsprung disease surgery - Kazez, Ahmet; Bakal, Ünal (Logos Medical Publishing, 2018)
Hirschsprung disease is one of the most common cause of distal bowel obstruction in newborn. Different surgical techniques are being used in its treatment Although different surgical techniques have been used, same essential anatomical points are taken into account and same functional results are expected. Late results are important because functional results come up late. In this article, late surgical results of different techniques in the literature were reviewed. © 2018 Logos Medical Publishing. All Rights Reserved.
Hirschsprung hastali?i cerrahisinin geç dönem sonuçlari
Keywords: Hirschsprung disease; Late period; Surgical results